2008
DOI: 10.1098/rstb.2008.0249
|View full text |Cite
|
Sign up to set email alerts
|

Introduction. Ecological immunology

Abstract: An organism's fitness is critically reliant on its immune system to provide protection against parasites and pathogens. The structure of even simple immune systems is surprisingly complex and clearly will have been moulded by the organism's ecology. The aim of this review and the theme issue is to examine the role of different ecological factors on the evolution of immunity. Here, we will provide a general framework of the field by contextualizing the main ecological factors, including interactions with parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
193
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(196 citation statements)
references
References 148 publications
(191 reference statements)
2
193
0
1
Order By: Relevance
“…The idea that disease resistance is costly and is traded off against other traits, such as reproductive effort and longevity, is fundamental to the field of ecological immunology (e.g. (Lochmiller and Deerenberg, 2000;Owens and Wilson, 1999;Schulenburg et al, 2009;Sheldon and Verhulst, 1996;Wilson, 2005) Norris & Evans 2000; Wilson 2005). In order to test this hypothesis, immune-related costs must be experimentally distinguished from other pathological processes associated with infection.…”
Section: Nutrition and The Consequences Of Immune Trade-offsmentioning
confidence: 99%
“…The idea that disease resistance is costly and is traded off against other traits, such as reproductive effort and longevity, is fundamental to the field of ecological immunology (e.g. (Lochmiller and Deerenberg, 2000;Owens and Wilson, 1999;Schulenburg et al, 2009;Sheldon and Verhulst, 1996;Wilson, 2005) Norris & Evans 2000; Wilson 2005). In order to test this hypothesis, immune-related costs must be experimentally distinguished from other pathological processes associated with infection.…”
Section: Nutrition and The Consequences Of Immune Trade-offsmentioning
confidence: 99%
“…However, a growing body of empirical work in the field of ecological immunology has shown that immune parameters in insects respond to various ecological factors, and may be induced on time scales relevant to the individual's fitness (Best et al, 2013;Rolff and Siva-Jothy, 2003;Schmid-Hempel, 2003;SchmidHempel, 2005;Schulenburg et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…An alternative, and not necessarily contradictory, adaptationist approach recognizes that anti-pathogen defences are energetically costly to the organism, and that systems of defence can be expected to develop in response to ecological factors across the life course (Sheldon & Verhulst 1996;Schulenburg et al 2009). CRP is an important component of innate immunity, and is involved in activating complement, promoting phagocytic activity and opsonizing bacteria, fungi and parasites.…”
Section: Introductionmentioning
confidence: 99%